Geological characteristics of Chang’E-6 landing area in micro-scale unveiled by new observation data - Wei Yan; Xingguo Zeng; Xin Ren; Wangli Chen; Xingye Gao; Wei Zuo; Bin Liu; Zhoubin Zhang; Qiang Fu; Jianjun Liu; Chunlai Li (Nature Communications)
Abstract Chang’E-6 mission successfully achieved humanity’s first sample return from the farside of the Moon. Here, we report a high-precision terrain dataset with millimeter-to-decimeter spatial resolution around the CE-6 landing site. Based on this dataset, the accurate location of the landing site is determined to be (153.9776° W, 41.6251° S, -5273 m), and a micro-scale geological analysis of the landing area is conducted. Comparative analysis suggests that the surface exposure time of Chang’ E-6 landing area is likely between that of Chang’E-4 and Chang’E-5 landing areas. Studies of the ejecta thickness from possible craters in mare and non-mare areas indicate that Chang’E-6 samples may contain materials from diverse provenances. Detailed topographic analysis reveals that the Chang’E-6 landing area is primarily covered by local mare materials, which were excavated from a nearby unnamed crater with a diameter of ~ 51 m and account for 30%–35% in volume.